Molecular Detection of Bacterial vaginosis Isolated from Preterm Labor Patients in Wasit City, Iraq - Alameer, Ibtihal N. Abd; Kabe, Muhamed Ali Al (South Eastern European Journal of Public Health, 2024)
The aim of this study was to evaluate the role of bacterial vaginosis in preterm labor. There is growing evidence that infections, particularly those that spread from the lower genital tract, might trigger preterm labor. One of the main causes of newborn morbidity and mortality is preterm birth. This is a cross-sectional study which was carried out in the labor facilities in local hospital in Wasit. A total 90 swab samples were collected by gynecologist from patients in Preterm and Full-term labor Bacteriological diagnosis was done using Molecular quantification methods have been reported recently, but the specific risk factors they might identify remain unclear. We carried our study on 90 pregnant women, divided into two groups. First group delivered preterm and other group at full term. There are 38 out of 45 women who had no bacterial infection in the group of full-term pregnancy compared to 19 out of 45 in the preterm group , so the incidence of BV was significantly more in preterm group. The commonest isolated pathogen was G. vaginalis, followed by Megasphaera and Atopobium vaginalis. More than one-third (37.8%) of patients with preterm delivery have Gardnerella infection when compared to only 6.7% of those who delivered at term , Around one-quarter (26.7%) of patients who delivered preterm were diagnosed with Megasphaera. Only 4.4% of full-term patients had positive tests for this infection and 22.2% of patients with preterm labour compared to 4.4% of full-term pregnancies diagnosed with Atopobium infection.